Odškodninska odgovornost za kršitev človekovih pravic - Zagorc, Saša (Pravni letopis, 2013)
Author analyses if the currect state of art in the case law of Slovenian courts, in particular the case law concerning Erased individuals, adequately resolves specifical issues of public liability for legislative acts where typical elements of civil liability, e.g. statute of limitations or limited amount of awarded damages, intertwine with constitutional concepts, such as protection of human rights and redress thereof. State liability for legislative acts has not been fully accepted in European legal systems. States avoid it not only for conceptual reasons but also due to pragmatic motifs which, as a consequence, reveal a schism between more pro-human rights oriented and utilitarian understanding of human rights in the society. Additionally, redress of human rights infringements by legislative action or omission raises also some concerns, particularly in case of systemic and long-lasting violations of human rights, if the former could seriously endanger the normal functioning of the state. In such situations the legislator may exceptionally step aside from full redress. However, burden of proof rests with legislator which entails a duty to demonstrate the exceptionality of the situation, the necessity (ultimaratio measure) whereat mere economic considerations will not be considered as sufficient by courts and, finally, lack of legitimate alternatives. In line with general overview, the draft lawon the redress of damage to the Erased individuals does not meet these standards.
Keywords: človekove pravice; država; human rights; kršenje; odškodnina; odškodninska odgovornost; state